Industrial electronics - Kissell, Thomas E. (Prentice Hall, 1997)
This survey of industrial electronics focuses on actual (not theoretical) working circuits, and provides real, common industrial applications for each component, circuit, and system, explaining how the devices operate and are tested in typical, on-the-job assignments. Focused on the latest technology, the text reflects the author's knowledge drawn from 20 years of experience working on automated industrial systems, teaching the theory and operation of these systems in a traditional college setting, and consulting directly to technicians and engineers currently working on these systems in industry. The text offers coverage of modern circuits, such as variable frequency drives, DC drives and stepper and servo amplifiers and drives, providing modern industrial applications for each device, control circuit, and system discussed and that students will encounter on-the-job. It also contains explanations of interfacing electronic systems, from programmable controllers, and robots to networks and other examples of data communications.